Twistor-like constraints for the superparticle and the superstring - Rocha, Luis Alberto Ypanaqué [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
In this work we study actions for the superparticle and the superstring using twistor-like constraints. We write BRST charges for the superparticle and the superstring in ten dimensions, and the BRST charge for a particle model in four dimensions in order to make some comparisons. We start showing how twistors appear as geometrical objects parametrizing SO(4)/U(2), and use a generalization of this fact to ten dimensions to construct the corresponding theories. We then show how to obtain the pure spinor superparticle and superstring actions in ten dimensions by gauge-twisting and gauge-fixing the initial theory.

Neste trabalho nós estudamos ações para a superpartícula e a supercorda usando vínculos twistóricos. Escrevemos as cargas BRST para a superpartícula e a supercorda em dez dimensões, e a carga BRST para um modelo de partícula em quatro dimensões com a finalidade de fazer algumas comparações. Começamos mostrando como os twistors aparecem como objetos geométricos que parametrizam SO(4)/U(2), e usamos uma generalização deste fato para dez dimensões e assim construir as teorías correspondentes. Então mostramos como obter as ações de espinores puros para a superpartícula e a supercorda em dez dimensões por meio de gauge-twisting e gauge-fixing da teoría inicial.
Vínculos twistóricos para a superpartícula e a supercorda
Keywords: Superpartícula; Supercorda; Twistors; Espinores puros; Método BRST